The Attack of the Grizzlies, 1967 Book 17 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic Inc., 2018)
Eleven-year-old Melody Vega and her family visit Glacier National Park every summer, but this year Mel comes face- to-face with a terrifying grizzly bear.
Keywords: Bear attacks -- Montana; Glacier National Park; Juvenile fiction; Human-bear encounters -- Montana; Glacier National Park; Juvenile fiction; Camping -- Montana; Glacier National Park; Juvenile fiction; Grizzly bear -- Juvenile fiction; Human-bear encounters -- Montana; Glacier National Park; Juvenile literature; Bear attacks -- Montana; Glacier National Park; Juvenile literature; Historical fiction -- Juvenile fiction